Predictors for Fear of Cancer Recurrence in Breast Cancer Patients Referred to Radiation Therapy During the COVID-19 Pandemic: A Multi-Center Cross-Section Survey - Xie, Jinrong; Qi, Weixiang; Cao, Lu; Tan, Yuting; Huang, Jin; Gu, Xiaodong; Chen, Bingguang; Shen, Peipei; Zhao, Yutian; Zhang, Ying; Zhao, Qingwen; Huang, Hecheng; et al. (Frontiers in Oncology, 2021)
Objective: The outbreak of COVID-19 pandemic has greatly impacted on radiotherapy (RT) strategy for breast cancer patients, which might lead to increased distressing psychological symptoms. We performed a multi-center cross-section survey to investigate prevalence of fear of cancer recurrence (FCR) and predictors for FCR in patients referred to RT during pandemic. Methods: 542 patients were consecutively enrolled from three regions in China including Yangtze Delta River Region, Guangdong and Shanxi province. Patients’ characteristics were collected using an information sheet, Fear of progression questionnaire-short form, Hospital Anxiety/Depression Scale and EORTC QLQ-C30. The hierarchical multiple regression models were performed. Results: 488 patients with complete data were eligible. The RT strategy was affected in 265 (54.3%) patients, including 143 with delayed RT initiation, 66 believing to have delayed RT initiation but actually not, 24 with RT interruptions, 19 shifting to local hospitals for RT and the remaining 13 influenced on both RT schedule and hospital level. The model explained 59.7% of observed variances in FCR (p<0.001) and showed that influence of RT strategy had significantly impacted on FCR (△R2=0.01, △F=2.966, p=0.019). Hospitals in Shanxi province (β=-0.117, p=0.001), emotional function (β=-0.19, p<0.001), social function (β=-0.111, p=0.006), anxiety (β=0.434, p<0.001) and RT interruption (β=0.071, p=0.035) were independent predictors. Conclusions: RT strategy for breast cancer patients was greatly influenced during pandemic. RT interruption is an independent predictor for high FCR. Our findings emphasize the necessity to ensure continuum of RT, and efforts should be taken to alleviate FCR through psychological interventions.